Functional differences in human aortic valve interstitial cells from patients with varying calcific aortic valve disease - Tuscher, Robin; Khang, Alex; West, Toni M.; Camillo, Chiara; Ferrari, Giovanni; Sacks, Michael S. (Frontiers in Physiology, 2023)
Calcific aortic valve disease (CAVD) is characterized by progressive stiffening of aortic valve (AV) tissues, inducing stenosis and insufficiency. Bicuspid aortic valve (BAV) is a common congenital defect in which the AV has two leaflets rather than three, with BAV patients developing CAVD decades years earlier than in the general population. Current treatment for CAVD remains surgical replacement with its continued durability problems, as there are no pharmaceutical therapies or other alternative treatments available. Before such therapeutic approaches can be developed, a deeper understanding of CAVD disease mechanisms is clearly required. It is known that AV interstitial cells (AVICs) maintain the AV extracellular matrix and are typically quiescent in the normal state, transitioning into an activated, myofibroblast-like state during periods of growth or disease. One proposed mechanism of CAVD is the subsequent transition of AVICs into an osteoblast-like phenotype. A sensitive indicator of AVIC phenotypic state is enhanced basal contractility (tonus), so that AVICs from diseased AV will exhibit a higher basal tonus level. The goals of the present study were thus to assess the hypothesis that different human CAVD states lead to different biophysical AVIC states. To accomplish this, we characterized AVIC basal tonus behaviors from diseased human AV tissues embedded in 3D hydrogels. Established methods were utilized to track AVIC-induced gel displacements and shape changes after the application of Cytochalasin D (an actin polymerization inhibitor) to depolymerize the AVIC stress fibers. Results indicated that human diseased AVICs from the non-calcified region of TAVs were significantly more activated than AVICs from the corresponding calcified region. In addition, AVICs from the raphe region of BAVs were more activated than from the non-raphe region. Interestingly, we observed significantly greater basal tonus levels in females compared to males. Furthermore, the overall AVIC shape changes after Cytochalasin suggested that AVICs from TAVs and BAVs develop different stress fiber architectures. These findings are the first evidence of sex-specific differences in basal tonus state in human AVICs in varying disease states. Future studies are underway to quantify stress fiber mechanical behaviors to further elucidate CAVD disease mechanisms.